Advances in Materials and Structures for Ingestible Electromechanical Medical Devices. Issue 52 (26th October 2018) - Bettinger, Christopher J.
Abstract: Ingestible biomedical devices that diagnose, prevent, or treat diseases has been a dream of engineers and clinicians for decades. The increasing apparent importance of gut health on overall well‐being and the prevalence of many gastrointestinal diseases have renewed focus on this emerging class of medical devices. Several prominent examples of commercially successful ingestible medical devices exist. However, many technical challenges remain before ingestible medical devices can achieve their full clinical potential. This Minireview summarizes recent discoveries in this interdisciplinary topic including novel materials, advanced materials processing techniques, and select examples of integrated ingestible electromechanical systems. After a brief historical perspective, these topics will be reviewed with a dedicated focus on advanced functional materials and fabrication strategies in the context of clinical translation and potential regulatory considerations. Future perspectives, challenges, and opportunities related to ingestible medical devices will also be summarized. Abstract : Ingestible medical devices could significantly improve human health. Recent examples of ingestible biomedical devices include edible cameras, biosensors, and drug delivery systems. This Minireview summarizes recent advances in materials, structures, fabrication techniques, and systems integration, which are relevant to the design of next‐generation ingestible biomedical devices. (Picture adapted from Bonacchini et al., Adv. Mat . 2018.)